Current understandings of the impact of mandatory vaccination laws in Europe. (4th May 2021) - Odone, Anna; Dallagiacoma, Giulia; Frascella, Beatrice; Signorelli, Carlo; Leask, Julie
ABSTRACT: Vaccinations are among the most successful preventive tools to protect collective health. In response to alarming vaccines preventable diseases (VPDs) outbreaks resurgence, decreased vaccination coverage and vaccine refusal, several European countries have recently revised their vaccination policies introducing or extending mandatory vaccinations. This review examines the health, political and ethical aspects of mandatory vaccination. The authors first clarify terms and definitions and propose a conceptual framework of mandatory policies. Second, they describe the current status of mandatory childhood immunization programmes in Europe, assessing selected mandatory laws. Third, as the authors conduct a systematic review of the literature (retrieving from Medline 17 relevant records between 2010 and 2020), they take an analytical approach to measure the impact of mandatory vaccination policies on both VPDs control and immunization coverage, but also on population attitudes toward vaccines. 40% of European countries currently have mandatory vaccination policies; however, policies vary widely and, although there is evidence of increased vaccine uptake, their impact on informed adherence to preventive behaviors is scant. Although mandatory vaccination policies might be needed to protect collective health in times of emergency, public health goals of VPD prevention and health promotion should primarily be pursued through health education and population empowerment.